Contribution to the study of insect stress hormones - Alquicer Barrera, Glenda Paola (Jihočeská univerzita, 2009)
The present study considers the versatile role of adipokinetic hormones (AKHs). Using the firebug Pyrrhocoris apterus as a model insect, the hypothesis that AKHs mediate stress response mechanisms was explored. The outcome indicated that there is a positive feedback regulation between an oxidative stressor action and the level of AKH in insect body, and that AKHs might be involved in the activation of antioxidant protection mechanism. Further results revealed a functional homology between AKH and the mammalian hormone glucagon. The possible effects of glucagon on mobilisation of energy reserves and on elicitation of an antioxidant response to oxidative stress were investigated. As a result, glucagon-immunoreactive material was detected for the first time in the firebug central nervous system and gut. Antioxidant mechanisms are elicited after glucagon treatment but it did not involve mobilization of energy reserves or AKH level changes. As a complement, the existence of a feedback between juvenile hormone and AKH was investigated by topical application of the juvenile hormone analogue methoprene, which influenced the release of AKH from the central nervous system into the haemolymph and induced a partial reduction of lipid content in haemolymph.
Contribution to the study of insect stress hormones
Keywords: adipokinetic hormone; glucagon; juvenile hormone analogue; stress hormones; oxidative stress; Pyrrhocoris apterus; adipokinetic hormone; glucagon; juvenile hormone analogue; stress hormones; oxidative stress; Pyrrhocoris apterus